Basic medical microbiology - Murray, Patrick R. (Elsevier, 2018)
Authored by the lead author of the bestselling Medical Microbiology and written in the same tradition, Basic Medical Microbiology was designed as a straight-forward, practical introduction to this difficult topic. It provides students with a firm foundation in the principles and applications of microbiology, serving as an effective prep tool for examinations and the transition into clinical application.